2016
DOI: 10.1002/2015jc011431
|View full text |Cite
|
Sign up to set email alerts
|

Optics of the offshore Columbia River plume from glider observations and satellite imagery

Abstract: The Columbia River (CR) is the largest source of freshwater along the U.S. Pacific coast. The resultant plume is often transported southward and offshore forming a large buoyant feature off Oregon and northern California in spring‐summer—the offshore CR plume. Observations from autonomous underwater gliders and Moderate Resolution Imaging Spectroradiometer (MODIS) satellite imagery are used to characterize the optics of the offshore CR plume off Newport, Oregon. Vertical sections, under contrasting river flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 63 publications
(88 reference statements)
1
14
0
Order By: Relevance
“…The model without assimilation reproduces the plume dynamics qualitatively correctly. For instance, the extent and geometry of the plume is similar to that revealed in satellite ocean color data (Saldías et al, ). Events of surface water freshening over the Oregon shelf following upwelling wind relaxation and reversal are observed at the NH10/NDBC46094 mooring (124.308°W, 44.634°N, see NDBC ).…”
Section: The Dynamical Regime and The Model Setupsupporting
confidence: 72%
See 1 more Smart Citation
“…The model without assimilation reproduces the plume dynamics qualitatively correctly. For instance, the extent and geometry of the plume is similar to that revealed in satellite ocean color data (Saldías et al, ). Events of surface water freshening over the Oregon shelf following upwelling wind relaxation and reversal are observed at the NH10/NDBC46094 mooring (124.308°W, 44.634°N, see NDBC ).…”
Section: The Dynamical Regime and The Model Setupsupporting
confidence: 72%
“…Glider temperature and salinity observations along the Newport line (44.65°N, see Figure ) are available on a grid with a 1‐km resolution in the horizontal direction, along the glider track, and 4 m in the vertical direction. The profiles are provided together with the variance of the raw observations for each point (Erofeev, ; Mazzini et al, ; Saldías et al, ). For each vertical profile the observations are boxed and averaged within each model grid cell.…”
Section: The Dynamical Regime and The Model Setupmentioning
confidence: 99%
“…So the fact that some reflectances are significant while others are not, within the studied period (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017), is probably a result of different dispersal in mixing conditions experimented by the plume. In any case, it is difficult to produce ESS estimates using a single ocean color band because optical properties related to SSS tend to show a nonlinear spatial variability (Saldías et al, 2016). Despite these complexities, the reconstructed monthly climatology using the ESS (Figure 4) captures all the main surface mesoscale features, particularly those related to the main path of the low-salinity water.…”
Section: Empirical Surface Salinitymentioning
confidence: 99%
“…The necessity to account for the large diversity of constituents found in plume waters (apart from DOM) that covary with salinity limits the interpretation of SSS fields based on adg443 alone. One can also argue that this approach may fail to detect the complex and rapid changes in SSS observed in the river plume (Geiger et al, 2013;Saldías et al, 2016), when the assumed conservative mixing between high CDOM river water and ocean water may not hold. Salisbury et al (2011), for example, reported large variability of the relation between salinity and absorption coefficient of colored detrital matter at 443 nm (a cdm 443) in the first 500 km of the Amazon river plume.…”
Section: Empirical Surface Salinitymentioning
confidence: 99%
“…Wind forcing also drives fluctuations in surface currents, water properties, and sea level, with typical scales of variability on the order of three to 10 days (Hickey and Banas, 2003). Additionally, upwelling-favorable winds drive crossshelf transport that actively pushes the freshwater plume of the Columbia River southward and offshore of the Oregon shelf in the spring and summer months (Barnes et al, 1972;Hickey et al, 2005;Saldías et al, 2016).…”
Section: Introductionmentioning
confidence: 99%